2017
DOI: 10.1016/j.commatsci.2016.10.046
|View full text |Cite
|
Sign up to set email alerts
|

Selecting reliable interatomic potentials for classical molecular dynamics simulations of glasses: The case of amorphous SiO2

Abstract: This paper presents an approach to judge the quality of classical interatomic potentials used in molecular dynamics simulations of glasses. The static structure and dynamical properties of amorphous SiO 2 were simulated by classical molecular dynamics using a series of well known interatomic potentials. Theoretical X-ray and neutron structure factors and effective neutron-weighted vibrational density of states of amorphous SiO 2 were computed from the obtained atomistic configurations and quantitatively compar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(6 citation statements)
references
References 25 publications
1
5
0
Order By: Relevance
“…The RDF comparison in Figure 6(a) clearly show a good agreement between our model and existing theoretical models as well as the experimental RDF 33 . The first peak at 1.59 Å is due to the Si-O bond length followed by second peak at 2.6 Å due to the O-O distance in tetrahedral motif.…”
Section: Figure 5: Showing the Connections Among Basic Building Block...supporting
confidence: 81%
“…The RDF comparison in Figure 6(a) clearly show a good agreement between our model and existing theoretical models as well as the experimental RDF 33 . The first peak at 1.59 Å is due to the Si-O bond length followed by second peak at 2.6 Å due to the O-O distance in tetrahedral motif.…”
Section: Figure 5: Showing the Connections Among Basic Building Block...supporting
confidence: 81%
“…Since silica is a glass former of prime importance, a large variety of interatomic potentials has been designed to investigate its structural and dynamical properties [12][13][14][15][16]. Among them, pairwise potentials with partial charges have been extensively used, since they allow, for a reasonable calculation cost, to model glass samples containing up to several hundreds of thousands atoms during millions of timesteps.…”
Section: Interatomic Potentialmentioning
confidence: 99%
“…Among the fixed-charge force fields, the van Beest, Kramer, and van Santen (BKS) model has been widely used to simulate both crystalline and amorphous silica due to its reliability in predicting both structure and dynamics. A detailed study carried out by Horbach and Kob of BKS simulations of melting silica found that both static and dynamical properties are in very good agreement with the experiment . Furthermore, BKS is a well-studied force field and has spawned interest in the development of other force fields of a similar potential form. ,, Although BKS was one of the earliest force fields developed for silica simulations, it is robust in predicting the realistic silica structure in both bulk and slab configurations. It is for these reasons that we use the BKS force field to obtain models for amorphous silica slabs in the present work.…”
Section: Introductionmentioning
confidence: 99%